Effects of realgar-indigo naturalis formula on a zebrafish tumor xenograft model induced by human acute promyelocytic leukemia cells: antitumor activity, hepatotoxicity, and transcriptomic analysis - Bai, Donghan; Zhang, Zihao; Gao, Jingyue; Wang, Qiaochu; Macdonald, Remy; Xu, Ziwen; Chen, Shumin; Huang, Nanxi; Luo, Lu (Frontiers in Pharmacology, 2025)
BackgroundLeukemia is a malignant hematologic disease that poses a serious threat to human health. Realgar-Indigo Naturalis formula (RIF), a traditional Chinese medicine formula, have demonstrated anti-tumor activity, but its mechanisms of action remain unclear.ObjectiveThis study aimed to establish a zebrafish HL-60 tumor transplantation model to investigate the anti-leukemic effects of RIF and explore its underlying mechanisms.MethodsThe zebrafish HL-60 tumor transplantation model was established, with RIF as the intervention drug and all-trans retinoic acid (ATRA) as the control. Anti-tumor efficacy was assessed via pharmacodynamic analysis. Transcriptomic analysis further elucidated gene expression profiles, differentially expressed genes, and relevant biological pathways.ResultsRIF significantly reduced tumor cell fluorescence intensity, demonstrating anti-tumor efficacy. Additionally, it improved HL-60-induced liver damage in zebrafish, as evidenced by a reduction in fatty vacuolar degeneration in liver tissue. Transcriptomic analysis revealed that ATRA mainly affected the FoxO signaling pathway, PI3K-Akt signaling pathway, apoptosis, and complement and coagulation cascades in leukemia treatment. RIF primarily influenced the ubiquitin-proteasome system, ferroptosis, and glutathione metabolism. The combination of ATRA and RIF also affected autophagosome and lysosome pathways, in addition to the aforementioned pathways.ConclusionRIF exhibit significant anti-tumor effects through modulation of multiple pathways. This study provides a theoretical foundation for the potential clinical application of RIF in leukemia treatment.